Revisiting the phylogeny and taxonomy of Osmanthus (Oleaceae) including description of the new genus Chengiodendron - Li, Yong-Fu; Zhang, Min; Wang, Xian-Rong; Sylvester, Steven Paul; Xiang, Qi-Bai; Li, Xuan; Li, Meng; Zhu, Hong; Zhang, Cheng; Chen, Lin; Yi, Xian-Gui; Mao, Ling-Feng; et al. (Phytotaxa, 2020)
Osmanthus (Oleaceae) is considered one of the most confusing genera with regards to circumscription and phylogenetic placement of taxa within the subtribe Oleinae of Oleaceae, with controversies mainly focused on the attribution of section Leiolea. In the present study, we analyzed 71 samples that represent the broad taxonomic, biogeographic, and morphological patterns in the subtribe Oleinae. Based on concatenation of four plastid genes (trnL-F, trnT-L, trnS-G, and matK) and comparison with the ITS region, Bayesian Inference, Maximum Likelihood and Maximum Parsimony phylogenies were inferred. Morphological character traits and geographical distributions of taxa were also studied. These results provide strong support for the segregation of the Leiolea clade (Osmanthus marginatus, O. matsumuranus and O. minor) of sect. Leiolea from Osmanthus. Therefore, the Leiolea clade is instated as the new genus Chengiodendron, with a taxonomic treatment provided. This study provides a clearer understanding of the phylogenetic relationships of genera in the subtribe Oleinae.